Помножувачі частоти на напівпровідникових діодних структурах - Karushkin, M. F. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
Obvious advantages of the millimeter wave technology including a large information capacity, high directivity of radiation, diagnostics and spectroscopy capabilities of different environments, including the methods of electron paramagnetic resonance and high resolution nuclear magnetic resonance have led to the rapid development of techniques for that range throughout the world. These advantages determine the attractiveness of the practical application of millimeter wavelengths to create high-speed communication links, high-precision radar, chemicals identification device and other equipment.Important role in the development of millimeter and sub-millimeter wave ranges belongs to the frequency multipliers development. This paper analyzes the main trends of modern development of efficient frequency multipliers on semiconductor diode structures, which are based on different physical principles, namely diode harmonic generators; frequency multipliers based on nonlinear dependencies of their reactive parameters on the voltage; frequency multipliers of high multiplicity on IMPATT diodes operating in mode of pulse exciting oscillations at high frequencies; multipliers on complex heterostructures and quantum super lattices in the terahertz range.The paper presents design solutions for frequency multipliers with various configurations and ways of optimizing the diode structures and operation modes that ensure their effective functioning in the frequency multiplication mode. The connection of electric parameters of frequency multipliers with output characteristics of microwave devices is determined.The given review of the results on designing power sources based on multiplying diodes indicates significant advances in this field and rapid development of the electronic component base in the short-wave part of the microwave spectrum.Further development of the technique of multiplying diodes will move forward not only in the direction of increasing the working capacity, but also in solving the problem of microminiaturization. In this regard, the emergence of heteroepitaxial multilayer varactor structures should be noted. Such structures are made with molecular beam epitaxy and have all the advantages of a composite varactor, but at the same time have better thermal characteristics and good prospects for their applications in the terahertz range.